2013
DOI: 10.3402/tellusb.v65i0.19660
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of N<sub>2</sub>O emissions to the atmosphere from Indian monsoonal estuaries

Abstract: A B S T R A C T Estuaries are known to contribute a significant amount of nitrous oxide (N 2 O) to the atmosphere; however, the contribution from the Indian estuaries is unknown. We made an attempt to estimate emissions of N 2 O from the Indian estuaries by collecting samples from 28 major and minor estuaries along the Indian coast during the wet and dry periods. The N 2 O was mostly saturated in all measured Indian estuaries during the study period (72Á631%), with exceptionally high saturation in the Ponniyaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
(40 reference statements)
3
24
0
Order By: Relevance
“…Dissolved N 2 O concentrations were mostly close to atmospheric equilibrium concentrations (i.e., 100 % saturation), which is in line with other comparable studies in the tropics and subtropics (Richey et al, 1988;Zhang et al, 2010;Rao and Sarma 2013;Borges et al, 2015). High N 2 O concentrations were reported for eutrophic and hypoxic coastal waters in the western Indian continental shelf (up to 533 nmol L −1 ; Naqvi et al, 2000) and for the Peruvian upwelling (up to 986 nmol L −1 ; Arevalo-Martinez et al, 2015).…”
Section: N 2 Osupporting
confidence: 78%
See 1 more Smart Citation
“…Dissolved N 2 O concentrations were mostly close to atmospheric equilibrium concentrations (i.e., 100 % saturation), which is in line with other comparable studies in the tropics and subtropics (Richey et al, 1988;Zhang et al, 2010;Rao and Sarma 2013;Borges et al, 2015). High N 2 O concentrations were reported for eutrophic and hypoxic coastal waters in the western Indian continental shelf (up to 533 nmol L −1 ; Naqvi et al, 2000) and for the Peruvian upwelling (up to 986 nmol L −1 ; Arevalo-Martinez et al, 2015).…”
Section: N 2 Osupporting
confidence: 78%
“…flux densities between 0.7 and 49 mmol m −2 yr −1 in the estuaries of the Sundarban mangrove ecosystem. However, we caution that the comparison suffers from the different approaches to determining the gas exchange velocity k. Koné et al (2010), Shalini et al (2006), Biswas et al (2007), and Rao and Sarma (2013) used empirical equations relating k to wind speed, while we used estimates based on floating chamber measurements. We refer to our discussion in Müller et al (2016), where we showed that our estimates derived by floating chamber measurements yielded higher values than if we had used empirical relationships with wind speed.…”
Section: Chmentioning
confidence: 99%
“…Biogeochemical cycling over the inner shelves is to a large extent influenced by anthropogenic discharges from adjacent estuaries, the waters of which are expected to be highly supersaturated with N 2 O [ Barnes and Owens , ; Bange , ; Barnes and Upstill‐Goddard , ]. However, the Indian estuaries show low N 2 O concentrations due to their capacity for rapid assimilation of nitrogen [ Rao and Sarma , ]. The Kochi estuary is no exception to this and due to its very fast turnover times for anthropogenic nitrogen [ Bhavya et al ., ] its N 2 O concentrations are very low during both the dry (12 ± 5.6 nM) and wet (28 ± 15 nM) seasons (unpublished data), which is in agreement with earlier studies [ Rao and Sarma , ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the Indian estuaries show low N 2 O concentrations due to their capacity for rapid assimilation of nitrogen [ Rao and Sarma , ]. The Kochi estuary is no exception to this and due to its very fast turnover times for anthropogenic nitrogen [ Bhavya et al ., ] its N 2 O concentrations are very low during both the dry (12 ± 5.6 nM) and wet (28 ± 15 nM) seasons (unpublished data), which is in agreement with earlier studies [ Rao and Sarma , ]. Moreover, most of our nearshore observations were made during the flood tide (see Table of Gupta et al .…”
Section: Discussionmentioning
confidence: 99%
“…3f). The significant north-south variations in physical associated with biogeochemical properties along the east coast of India were mainly driven from discharge from various rivers with different characteristics (Sarma et al, 2012a,b;Rao and Sarma, 2013).…”
Section: Physicochemical Propertiesmentioning
confidence: 98%